SYNTHETIC CANNABINOID AND KIDNEY - Ozdemir, Erman; Ozdemir, Pinar Kutluturk; Ozdemir, Erdogan; Mese, Meral; Parmaksiz, Ergun; Boz, Gulsah; Bahcebasi, Zerrin Bicik (Oxford Univ Press, 2016)
[Abstract Not Available]
53rd ERA-EDTA Congress -- MAY 21-24, 2016 -- Vienna, AUSTRIA